The chloroplast genome of Salix floderusii and characterization of chloroplast regulatory elements - Ren, Weichao; Jiang, Zhehui; Zhang, Meiqi; Kong, Lingyang; Zhang, Houliang; Liu, Yunwei; Fu, Qifeng; Ma, Wei (Frontiers in Plant Science, 2022)
Salix floderusii is a rare alpine tree species in the Salix genus. Unfortunately, no extensive germplasm identification, molecular phylogeny, and chloroplast genomics of this plant have been conducted. We sequenced the chloroplast (cp) genome of S. floderusii for the first time using second-generation sequencing technology. The cp genome was 155,540 bp long, including a large single-copy region (LSC, 84,401 bp), a small single-copy region (SSC, 16,221 bp), and inverted repeat regions (IR, 54,918 bp). A total of 131 genes were identified, including 86 protein genes, 37 tRNA genes, and 8 rRNA genes. The S. floderusii cp genome contains 1 complement repeat, 24 forward repeats, 17 palindromic repeats, and 7 reverse repeats. Analysis of the IR borders showed that the IRa and IRb regions of S. floderusii and S. caprea were shorter than those of S. cinerea, which may affect plastome evolution. Furthmore, four highly variable regions were found, including the rpl22 coding region, psbM/trnD-GUC non-coding region, petA/psbJ non-coding region, and ycf1 coding region. These high variable regions can be used as candidate molecular markers and as a reference for identifying future Salix species. In addition, phylogenetic analysis indicated that the cp genome of S. floderusii is sister to S. cupularis and belongs to the Subgenus Vetrix. Genes (Sf-trnI, Sf-PpsbA, aadA, Sf-TpsbA, Sf-trnA) obtained via cloning were inserted into the pBluescript Ⅱ SK (+) to yield the cp expression vectors, which harbored the selectable marker gene aadA. The results of a spectinomycin resistance test indicated that the cp expression vector had been successfully constructed. Moreover, the aadA gene was efficiently expressed under the regulation of predicted regulatory elements. The present study provides a solid foundation for establishing subsequent S. floderusii cp transformation systems and developing strategies for the genetic improvement of S. floderusii.